MISYA: Sharia Financing System to Improve Human Resource Competency as Account Officers of Sharia Banks - Marlya Fatira AK; Mardelia Desfrida; Titis Budi Prihatin; Fauzi Arif Lubis (Proceeding of International Conference on Multidisciplinary Research, 2024)
This research was conducted to produce MISYA: Real Project Based Financing System Model. This model will be used for banking practices carried out in Sharia labs and conventional banking labs managed by the Medan State Polytechnic Accounting Department. MISYA will facilitate actual practice for every student when playing the role of the Bank's Account Officer position. This is one of the outcomes of project-based learning implementation to support professional and superior Polmed graduates. This research aims specifically to design a real project-based Financing system model using Microsoft Excel. The research method used is a combination method. Qualitatively, data was collected through literature studies, observations, and interviews, designing MISYA, carrying out MISYA trials, and conducting Focus Group Discussions in implementing MISYA. Technology Readiness Level: this research is on a scale of 4 (four). The research method used is a qualitative research method, with explanations in the form of descriptive and explanatory. After going through the data collection and processing stages, research results showed an increase in student competency after using MISYA to understand the job position of an Account Officer at a Sharia bank. Increased ability and competency occurred for 92% of students who participated in socialization using MISYA. In addition, it was found that the Sharia Finance and Banking Study Program has solid and consistent efforts to improve the competency of its graduates for graduate learning outcomes. The MISYA Model design has accommodated the Account Officer process in serving customer financing applications from receipt, data input, and initial stage analysis to final stage analysis or financing approval. The practicum learning curriculum content to strengthen Account Officer competency in the Sharia Finance and Banking Study Program has been adjusted to enrich and add practical content, as well as implementing Case Base Learning by adding cases of financing applications and SLIK examinations from prospective customers.